Gonadal development and gametogenesis in the threatened freshwater siluroid fish Horabagrus brachysoma (Gunther, 1864): a morpho-histological perspective - Chandran, Lekshmi R.; Prasad, G. (Indian Journal of Fisheries, 2018)
The macro-morphology and histology of the reproductive system together with cytology of the process of gametogenesis in Asian sun catfish, Horabagrus brachysoma (Gunther, 1864) were investigated. A maturity key for horabagrids, based on macroscopic appearance of gonads at different stages of maturity was established for the first time. The distinctive features of male genital system were the digitiform testes, absence of seminal vesicles and five morphological maturity stages. Unrestricted semicystic spermatogenic activity with seven cytological stages was recognised viz., primordial germ cells, primary spermatogonia, secondary spermatogonia, primary spermatocytes, secondary spermatocytes, spermatids and spermatozoa. The classic cystovarian, group synchronic ovary, with five morphological maturity stages and a single spawning period were the peculiarities of female reproduction. The process of oogenesis progressed through five phases viz., previtellogenic, cytoplasmic growth, vitellogenic, yolky and mature. The sequence of oocyte maturation was: oogonia, chromatin nuclear, peri-nuclear, cortical alveolar, yolky and mature. Vitellogenesis was initiated in oocytes of maturing or stage-Il ovary. No liqueification of yolk was observed. Atresia was observed in vitellogenic and mature oocytes only. Corpus luteum like structure was present in ovaries with vitellogenic and yolky oocytes. A very prominent zona radiata of thickness 16.5 Î¼m covered mature oocytes.